Fundamental Factors and Systematic Risk on Stock Return in Indonesia Construction and Infrastucture Firms 2021-2023 - Erlansyah, Marsya Batrisyia; Irfandy, Keysha Putri; Fransiska, Nurlia; Nopelita, Eva; Puttri, Daniati; Darmayanti, Yeasy (International Journal of Scientific Research and Management (IJSRM), 2025)
This research aims to analyze the effect of fundamental ratios (current ratio, debt to total assets ratio, earnings power to total investment, and fixed assets turnover) on stock returns, with coefficient beta as a moderator for construction and infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study uses 204 observation data obtained from the official website of the Indonesia Stock Exchange and processed with multiple linear regression analysis and moderated regression analysis (MRA) techniques. The research concludes that current ratio (CR), debt to total assets ratio, and earnings power of total investment significantly affect stock returns, while fixed asset turnover does not affect stock returns. Additionally, stock beta moderates the relationship between EPTI and stock returns, but does not moderate the relationship between CR, DAR, or FAT and stock returns. This indicates that investment efficiency becomes more relevant in conditions of high market risk, while liquidity, leverage, and asset efficiency remain unaffected by fluctuations in systematic risk.